Everyday ontologies and Islam for childless women in northwestern Turkey. Issue 1 (2nd January 2018) - Göknar, Merve
ABSTRACT: This article discusses the significance of everyday Islam as a gendered locus for socialisation. Religious practices and conversations about religion comprise a major part of quotidian activities in the two villages in northwestern Turkey where the research took place. Men and women's everyday interaction with Islam dominated their ways of thinking, acting and especially socialising. Exploring the ways in which the Qur'an and the Hadith as discursive resources of Islam influence power relations and everyday practices, the article argues that Islamic morality co-exists with everyday Islam.